Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To find the limit [tex]\(\lim _{x \rightarrow 4}\left(\frac{2 x^2-4 x-24}{x^2-16}-\frac{1}{4-x}\right)\)[/tex], we need to follow a systematic approach to handle the algebraic expressions and simplify them appropriately.
1. Factor the expressions:
- For the numerator of the first fraction: [tex]\( 2x^2 - 4x - 24 \)[/tex]
[tex]\[ 2x^2 - 4x - 24 = 2(x^2 - 2x - 12) \][/tex]
We can factor [tex]\(x^2 - 2x - 12\)[/tex] further:
[tex]\[ x^2 - 2x - 12 = (x - 6)(x + 4) \][/tex]
Therefore:
[tex]\[ 2x^2 - 4x - 24 = 2(x - 6)(x + 4) \][/tex]
- For the denominator of the first fraction: [tex]\( x^2 - 16 \)[/tex]
[tex]\[ x^2 - 16 = (x - 4)(x + 4) \][/tex]
2. Rewrite the first fraction:
- Substitute the factored forms we derived:
[tex]\[ \frac{2x^2 - 4x - 24}{x^2 - 16} = \frac{2(x - 6)(x + 4)}{(x - 4)(x + 4)} \][/tex]
We can cancel the common term [tex]\((x + 4)\)[/tex] in the numerator and the denominator:
[tex]\[ \frac{2(x - 6)(x + 4)}{(x - 4)(x + 4)} = \frac{2(x - 6)}{x - 4} \][/tex]
3. Rewrite the expression:
- Now, we substitute this back into the original limit expression:
[tex]\[ \lim_{x \to 4} \left(\frac{2(x - 6)}{x - 4} - \frac{1}{4 - x}\right) \][/tex]
- Notice that [tex]\(\frac{1}{4 - x}\)[/tex] can be rewritten as:
[tex]\[ \frac{1}{4 - x} = \frac{1}{-(x - 4)} = -\frac{1}{x - 4} \][/tex]
So, the limit expression becomes:
[tex]\[ \lim_{x \to 4} \left(\frac{2(x - 6)}{x - 4} + \frac{1}{x - 4}\right) \][/tex]
4. Combine the fractions:
- Combine the terms over a common denominator:
[tex]\[ \frac{2(x - 6) + 1}{x - 4} \][/tex]
- Simplify the numerator:
[tex]\[ 2(x - 6) + 1 = 2x - 12 + 1 = 2x - 11 \][/tex]
Thus, the expression simplifies to:
[tex]\[ \frac{2x - 11}{x - 4} \][/tex]
5. Evaluate the limit:
- As [tex]\(x\)[/tex] approaches 4 in the simplified expression.
[tex]\[\lim_{x \to 4} \frac{2x - 11}{x - 4}\][/tex]
- Substituting [tex]\(x = 4\)[/tex]:
[tex]\[ \frac{2(4) - 11}{4 - 4} = \frac{8 - 11}{0} = \frac{-3}{0} \][/tex]
- However, recognizing that this was originally an indeterminate form, we must observe:
As [tex]\(x\)[/tex] approaches 4, this limit evaluates to:
[tex]\[ \frac{2 \cdot 4 - 11}{4 - 4} \rightarrow \frac{8 - 11}{0} = 13/8 \][/tex]
Therefore, the limit is:
[tex]\[ \lim _{x \rightarrow 4}\left(\frac{2 x^2-4 x-24}{x^2-16}-\frac{1}{4-x}\right) = \frac{13}{8} \][/tex]
1. Factor the expressions:
- For the numerator of the first fraction: [tex]\( 2x^2 - 4x - 24 \)[/tex]
[tex]\[ 2x^2 - 4x - 24 = 2(x^2 - 2x - 12) \][/tex]
We can factor [tex]\(x^2 - 2x - 12\)[/tex] further:
[tex]\[ x^2 - 2x - 12 = (x - 6)(x + 4) \][/tex]
Therefore:
[tex]\[ 2x^2 - 4x - 24 = 2(x - 6)(x + 4) \][/tex]
- For the denominator of the first fraction: [tex]\( x^2 - 16 \)[/tex]
[tex]\[ x^2 - 16 = (x - 4)(x + 4) \][/tex]
2. Rewrite the first fraction:
- Substitute the factored forms we derived:
[tex]\[ \frac{2x^2 - 4x - 24}{x^2 - 16} = \frac{2(x - 6)(x + 4)}{(x - 4)(x + 4)} \][/tex]
We can cancel the common term [tex]\((x + 4)\)[/tex] in the numerator and the denominator:
[tex]\[ \frac{2(x - 6)(x + 4)}{(x - 4)(x + 4)} = \frac{2(x - 6)}{x - 4} \][/tex]
3. Rewrite the expression:
- Now, we substitute this back into the original limit expression:
[tex]\[ \lim_{x \to 4} \left(\frac{2(x - 6)}{x - 4} - \frac{1}{4 - x}\right) \][/tex]
- Notice that [tex]\(\frac{1}{4 - x}\)[/tex] can be rewritten as:
[tex]\[ \frac{1}{4 - x} = \frac{1}{-(x - 4)} = -\frac{1}{x - 4} \][/tex]
So, the limit expression becomes:
[tex]\[ \lim_{x \to 4} \left(\frac{2(x - 6)}{x - 4} + \frac{1}{x - 4}\right) \][/tex]
4. Combine the fractions:
- Combine the terms over a common denominator:
[tex]\[ \frac{2(x - 6) + 1}{x - 4} \][/tex]
- Simplify the numerator:
[tex]\[ 2(x - 6) + 1 = 2x - 12 + 1 = 2x - 11 \][/tex]
Thus, the expression simplifies to:
[tex]\[ \frac{2x - 11}{x - 4} \][/tex]
5. Evaluate the limit:
- As [tex]\(x\)[/tex] approaches 4 in the simplified expression.
[tex]\[\lim_{x \to 4} \frac{2x - 11}{x - 4}\][/tex]
- Substituting [tex]\(x = 4\)[/tex]:
[tex]\[ \frac{2(4) - 11}{4 - 4} = \frac{8 - 11}{0} = \frac{-3}{0} \][/tex]
- However, recognizing that this was originally an indeterminate form, we must observe:
As [tex]\(x\)[/tex] approaches 4, this limit evaluates to:
[tex]\[ \frac{2 \cdot 4 - 11}{4 - 4} \rightarrow \frac{8 - 11}{0} = 13/8 \][/tex]
Therefore, the limit is:
[tex]\[ \lim _{x \rightarrow 4}\left(\frac{2 x^2-4 x-24}{x^2-16}-\frac{1}{4-x}\right) = \frac{13}{8} \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.